Safeguarding Interorganizational Performance and Continuity Under Ex Post Opportunism - Jap, Sandy D.; Anderson, Erin (Management Science, 2003)
Opportunism is a central construct in exchange theory. Economists contend that despite the firm's best efforts to erect governance structures that reduce opportunism and preserve outcomes, there is always some opportunism that remains once the transaction is in place. Despite this, there are few studies that systematically investigate the safeguarding efficacy of relationship attributes in the presence of such ex post opportunism. In this research, we develop a theoretical framework and provide a longitudinal test of the ability of various relationship safeguards to preserve performance outcomes and future expectations given varying levels of ex post opportunism in the relationship. Our survey results from over 300 buyers and suppliers indicates that given lower levels of opportunism, bilateral idiosyncratic investments and interpersonal trust enhance performance outcomes and future expectations, while goal congruence has no discernable effect. However, at higher levels of opportunism, goal congruence becomes a more powerful safeguard, while interpersonal trust becomes less effective. Bilateral idiosyncratic investments continue to preserve performance outcomes and future expectations even at higher levels of opportunism. Implications for the long-term management of interorganizational alliances are discussed.